The Effect of Inflation, Liquidity, and Capital Structure on Financial Performance of Consumer Goods Companies Listed on IDX - Maria Trifonia Elensi Naja; Khairina Natsir (Graduate Program of Universitas Tarumanagara, 2023)
This study is intended to determine the empirical scientific evidence of the effect of inflation, liquidity, and capital structure on financial performance of consumer goods sector of companies listed on Indonesia Stock Exchange (IDX) in the period from 2016 to 2020. Financial performance is measured using ROE, while inflation is proxied by Indonesia’s annual inflation rate, liquidity is proxied by CR, and capital structure is proxied by DER. A total of 40 consumer goods companies were sampled in this research. The sample was selected using purposive sampling technique and resulted in a total of 200 observations. Data analysis was carried out using panel data regression using EViews 12 software. The results showed that inflation had a positive and significant effect on financial performance, liquidity had a negative and insignificant effect on financial performance, and capital structure had a positive and significant influence on financial performance of consumer goods companies listed on IDX.